Gas turbine theory - Cohen, Henry (Addison Wesley Longman, 1996)
Since publication of the third edition of Gas Turbine Theory, the gas turbine has been found to be suitable for an increasing number of applications. The fourth edition of this popular textbook has been revised and updated to reflect these developments. Gas turbines are becoming widely used for base-load electricity generation, as part of combined-cycle plant, and combined cycles receive more attention in this edition. There are now stringent statutory limits on harmful emissions, and the chapter on combustion has been enlarged to include a discussion of the factors affecting emissions and descriptions of current methods of attacking the problem. A section on coal gasification has also been added. Finally, the opportunity has been taken to make many small but significant improvements and additions to the text. The emphasis is still on fundamental principles, and readers must turn to the specialised literature for computational methods of dealing with the aerodynamic design of turbomachinery and the prediction of performance. Suitable as a coursebook for undergraduate and graduate students of mechanical and aeronautical engineering,Gas Turbine Theory will also continue to be a valuable reference for practising gas turbine engineers.